An eeploratory study of the HIV and Aids wellness context of a South African SME - Assimacopouls, Nadia (My University, 2013)
The current report was an exploratory case study that utilsed a mixed mehtodology to consider the HIV and Aids wellness context of a South African small to Medium Enterprise (SME), hereafter called company A. This study aimed to investigate company A by observing the knowledge. Attitude and practices (KAP) of emmployees, as well as their reported behaviours on disclosure of HIV status. HIV and AIDS are critical issues, with South Africa, having the highest rate in the world (UNAIDS, 2010). While various projects are in place to promote prevention and decrease infection rate, infection statistics plateaued at a high leve. The situation in South Africa thus needs to be examined from a different perspective, approaching the epidemic as a case study, rather than through the systematic models and interventions used in the past. A KAP survey and open ended questionnaire were used, as they formed the forefront of the assumptions usally in interventions that look at behaviour change model such as the Health belief model (HBM) and social cognitive theory (SCT) and the relationship between knowledge, attitude and practices and dissclosure of HIV status. The research observed that while no clear cut relationships can be found between knowwledge, attitude, practices, and the decisin of whether to dissclose the HIV status, the context and experience of the epidemic is far from straightforward, and needs to be tackled in it`s entiriety. While the intention of policies and interventions may be good, without the requisite investigation of the context, the attempts may not be as successfull as they could be.
Keywords: HIV, AIDS; South Africa; Knowledge, Attitude and Practices; Disclosure of HIV status ; Stigmatisation; Company Polices